Capillary electrophoresis methods for microRNAs assays: A review - Ban, Eunmi; Song, Eun Joo (ELSEVIER SCIENCE BV, 2014)
MicroRNAs (miRNAs) are short noncoding RNAs that conduct important roles in many cellular processes such as development, proliferation, differentiation, and apoptosis. In particular, circulating miRNAs have been proposed as biomarkers for cancer, diabetes, cardiovascular disease, and other illnesses. Therefore, determination of miRNA expression levels in various biofluids is important for the investigation of biological processes in health and disease and for discovering their potential as new biomarkers and drug targets. Capillary electrophoresis (CE) is emerging as a useful analytical tool for analyzing miRNA because of its simple sample preparation steps and efficient resolution of a diverse size range of compounds. In particular, CE with laser-induced fluorescence detection is a promising and relatively rapidly developing tool with the potential to provide high sensitivity and specificity in the analysis of miRNAs. This paper covers a short overview of the recent developments and applications of CE systems in miRNA studies in biological and biomedical areas. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: LASER-INDUCED FLUORESCENCE; NASOPHARYNGEAL CARCINOMA-CELLS; DIRECT QUANTITATIVE-ANALYSIS; MICROCHIP ELECTROPHORESIS; EXPRESSION PROFILES; MULTIPLE MICRORNAS; BINDING SITES; MESSENGER-RNA; DNA; SEPARATION